PENGARUH KELOMPOK ACUAN DAN PENGETAHUAN TENTANG PERBANKAN SYARI’AH TERHADAP MINAT MENABUNG DI PERBANKAN SYARI’AH SEMARANG - Arifatun Nisak; Saryadi Saryadi; Sri Suryoko (Jurnal Ilmu Administrasi Bisnis, 2013)
The government's efforts to boost growth in Indonesia islamic banks based on the fact that most of the Muslim community at this time look forward to a healthy banking system and reliable. In deciding to save in Islamic Banking, the reference group is one of the factors that can influence consumer decisions. In addition, consumer knowledge is also one of the elements of the psychological factors that influence consumer decisions. But, with the total of marketshare just 3.67 percent, total customer of Islamic bank are low for total customer of national banking in Indonesia. This study aims to determine the effect of reference group and knowledge to interest to have saving at Islamic Banking Semarang. The results showed that the total effect of reference group and knowledge on interest saving by 33.9 percent.